Essential journalism : the NCTJ guide for trainee journalists - Baker, Jonathan (Professor of journalism); National Council for the Training of Journalists (Great Britain) (London: Routledge, 2021)
"This book is a practical guide to all aspects of modern journalism for anyone seeking to study for the NCTJ Diploma and become a qualified journalist in the UK. Written in collaboration with the National Council for the Training of Journalists, Essential Journalism outlines everything you need to know about the journalism industry today, from its ethical framework to its practice across print, television, radio, online and social media. It looks at the core principles and the skills that are required of journalists across all platforms, helping students develop an overall understanding of the business and examining the application and adaptation of traditional best practice to the demands of the digital age. This is a unique one-stop shop for anyone who wants to understand the nature and purpose of journalism, and how it is changing and evolving in today's digital newsrooms. This book is a core resource for journalism trainees and undergraduates, as well as for seasoned practitioners and lecturers"--
The journalism landscape -- The nature of journalism. The nature of news -- You, the reporter -- Ethics -- Regulation -- The general reporter -- Storyfinding : Sources -- Storyfinding : Interviewing -- Storytelling : Anatomy of a news story -- Storytelling : Writing a news story -- Storytelling : Language and style -- Storytelling : Reporting numbers and statistics -- The digital journalist : the digital scene and writing for the website -- The digital journalist : social media and online research -- The radio journalist : the radio scene and writing for radio -- The radio journalist : news summaries and radio reporting -- The television journalist : the television scene and picture gathering -- The television journalist : continuous news and television reporting -- The print journalist -- The mobile journalist. The freelance journalist -- The feature writer -- The court reporter -- The political reporter -- The specialist reporter.
Includes bibliographical references and index.
Keywords: Journalism -- Handbooks, manuals, etc; Journalism -- Vocational guidance -- Great Britain